Modern endoscopic criteria for stratifiation of patients with atrophic gastritis in the development of precancerous changes of the stomach - Yu. M. Stepanov; O. V. Simonova; L. M. Mosiichuk; O. P. Petishko (Patologìâ)
Purpose: to identify the most signifiant endoscopic diagnostic criteria for the development of precancerous changes of the of the stomach mucosa (SM). Material and methods. 80 patients with atrophic gastritis were examined (34 (42.5 %) men and 46 (57.5 %) women, the average age (57.7 ± 2.1) years. The diagnosis was set during endoscopic examinations and was morphologically confimed in all cases. Esophagogastroduodenoscopy was performed using EVIS EXERA III video endoscopic system with Olympus 190 gastroscope (Japan). Examination of the stomach was carried out in white light regimen, magnifiation (near focus) and NBI regimen. All examined patients were divided into groups according to the presence and prevalence of intestinal metaplasia (IM) and the presence of SM dysplasia: group I – SM atrophy without IM (10 patients), II – SM atrophy with IM, limited of the antral part (20 patients), III – SM atrophy with diffse (multifocal) IM (39 patients), IV – SM dysplasia (11 patients). Results. For the formation of group of patients with high risk of developing gastric cancer, diagnostic criteria of structural changes of gastric mucosa with pre-cancerous potential were identifid. In white light upper endoscopy, the knotted / tuberous relief of the stomach mucosa can be considered as a diagnostic criterion for sensitivity (81.4 %) and specifiity (60.0 %) indicators. The xanthomatosis of the stomach mucosa increases by 5 times the risk of IM or dysplasia in patients with atrophic gastritis (sensitivity – 47.1 %, specifiity – 90.0 %). Magnifiation endoscopy and endoscopy with narrow-band imaging allowed us to establish another diagnostic criterion for the formation of the group with high risk of developing gastric cancer: pyloric metaplasia (pseudopylorisation) of the gastric corpus. Pyloric metaplasia increases the frequency of detection of structural precancerous changes in a patient with atrophic gastritis by almost 7 times (sensitivity – 71.4 %, specifiity – 70.0 %). Conclusion. The established endoscopic criteria (nodular relief of the stomach (OR = 4.96), xanthomatosis of the stomach (OR = 4.94), pyloric metaplasia of the stomach body (OR = 6.72)) can be applied in the formation of a group of patients with atrophic gastritis who have high potential for the development of gastric cancer and require careful examination using modern endoscopic equipment and dynamic surveillance.